Lactococcus Lactis D4 Starter Fermented Milk’s Effect on Liver Function of Obstructive Jaundice Model - Hannan Khairu Anami; M. Iqbal Rivai; Avit Suchitra; Irwan Irwan; Rini Suswita; Juni Mitra (Indonesian Journal of Multidisciplinary Science, 2023)
Obstructive jaundice can cause liver function damage which exacerbates patient morbidity and mortality. Fermented milk starter Lactococcus Lactis D4 derived from dadih is a probiotic that has the potential to improve liver function through the enterohepatic pathway. The research would like to determine the effect of Lactococcus Lactis D4 starter fermented milk on liver function of obstructive jaundice. This study was an experimental study with a post test only randomized control group design in 3 groups of Rattus Novergicus strain Wistar rats with obstructive jaundice model which got ligation of biliary ducts and given Lactococcus lactis D4 starter fermented milk for 7 days. Liver function was assessed by looking at the levels of total bilirubin, SGOT, SGPT, ALP, and GGT in each treatment group. Administration of Lactococcus Lactis D4 starter fermented milk caused a decrease in SGOT levels (LDB + BAL vs LDB: 51.12 ± 1.77 U/L vs 64.63 ± 0.10 U/L, p<0.05) and SGPT (LDB + LAB vs LDB: 60.60±0.85 U/L vs 67.77±2.60 U/L, p<0.05) which was significant. However, there was no significant effect on total bilirubin levels (LDB + BAL vs LDB: 3.21±0.11 mg/dl vs 3.18±0.10 mg/dl, p>0.05), ALP (LDB + LAB vs LDB: 108.20 ± 2.78 U/L vs 115.38 ± 5.08 U/L, p>0.05), and GGT (LDB + LAB vs LDB: 12.57 ± 0.45 U/L vs 12.78±0.31 U/L,  p>0.05). Lactococus Lactis D4 starter fermented milk can improve liver function which is indicated by a decrease in SGOT and SGPT levels in experimental animals.